Principal Supervision Competence in Secondary School in Lagos Central Senatorial District - Onikoyi, Olawale Abayomi (Jurnal Pendidikan Indonesia Gemilang, 2025)
The study investigated principal supervision competence in Lagos central senatorial district secondary schools. The research design used for the study was a descriptive survey. One hypothesis was developed, along with two research questions. There were 225 responses in the sample size. The teachers were chosen randomly, and fifteen items were used as the data gathering tool. The mean and standard deviation were used to analyze the data to answer the research questions, and the t-test was used to evaluate the hypotheses at 0.05. The research's findings showed how important it is to analyze the principal's supervision in secondary schools. As a result, suggestions were made that the Lagos State Ministry of Education constantly remind principals that their roles should be to support teachers rather than to criticize them. The Lagos state government should assign more qualified and capable principals to meet the burdens of principals' aiming at teachers. Additionally, the principal should always make helpful suggestions and respect the best advice teachers need. All of these things should be done to help teachers advance their teaching skills through collaboration with teachers.